Development of wearable rehabilitation device for wristfinger mobility rehabilitation - Tan, Chia Wen (2022)
Many hand rehabilitation systems have only one preprogramed exercise protocol, do not measure the recovery progress, are costly, heavy and also do not have built-in safety mechanisms. Therefore, the aim of this study is to design and construct an affordable and light-weight hand rehabilitation exoskeleton system that could provide continuous passive movement to the finger and wrist joints, allow the patient to choose between different rehabilitation protocols and review their recovery progress. The rehabilitation system constructed incorporated ESP32, flex sensors, MG995 servo motors and android mobile application. Moreover, origami string theory and 3D printing technology was integrated into the transmission mechanism design. From the results obtained, the transmission mechanism can actuate MCP and PIP flexion and extension as well as radiocarpal extension movements that respect the static constraints of the hand and do not exceed the maximum angular velocities that can be naturally generated. In addition, the transmission mechanism was capable of actuating movements at 3 different angular velocities. Furthermore, the sensing system could measure maximum angle values that have an accuracy comparable to other studies except for 0° angles. Next, the total cost of the rehabilitation system was RM 533.70 and the segments attached to the hand weighed only 250 g. In conclusion, all the objectives were met. In the future, the transmission mechanism can be improved to generate more torque, formfitting gloves and goniometers can be used to increase the accuracy of the sensing system and a cloud database could be used to track recovery progress of patients.